Increased MT2-MMP expression in gastric cancer patients is associated with poor prognosis - Xu, Xiaoli (Int J Clin Exp Pathol, 2015)
Matrix metalloproteinases (MMPs) are a family of proteolytic enzymes that contribute to tumorigenesis and metastasis due to their ability to degrade the extracellular matrix (ECM) and basement membrane. In despite of many reports in other solid tumors, the role of membrane type-2 MMP (MT2-MMP) in gastric cancer (GC) remains to be elucidated. The aim of this study was to investigate MT2-MMP expression in human GC tissue microarray (TMA) samples using immunohistochemistry (IHC). We found that MT2-MMP expression in tumor tissues was significantly higher compared to peritumoral tissues (P < 0.01). However, there were no statistically significant differences between MT2-MMP expression and clinicopathological parameters. In addition, univariate and multivariate Cox regression analysis showed GC patients with high MT2-MMP expression have poor overall survival (OS) compared to patients with low MT2-MMP expression (P = 0.013, P = 0.040, respectively). In conclusion, MT2-MMP is involved in GC invasion and metastasis and may serve as an independent prognostic factor for GC patients.